A study on genetic diversity of bagrid catfish (Hemibagrus guttatus Lacepede, 1803) using microsatellite markers - My, Bùi Hà; Hương, Nguyễn Thị; Đức, Nguyễn Hữu; Thúy Hà, Trần Thị (Vietnam Journal of Biotechnology, 2018)
Bagrid catfish (Hemibagrus guttatus Lacepede, 1803) is a wild species of high economic value in Northern Vietnam. Artificial reproduction of bagrid catfish requires sources of quality fingerlings in terms of genetics. In fact, bagrid catfish is endangered due to overhunting. Until now, studying on bagrid catfish was mainly focused on biology characterictics and artificial breeding. In this study, three microsatellite markers were used to assess the genetic characteristics of four bagrid catfish populations (three wild populations collected in Tuyên Quang, Phu Tho, Ha Giang and a cultured population in Hai Duong). These markers were registed Genbwith the code of KJ873116, KJ873117 and NC 023976 for HM7, HM8 and SS1, respectively. All of the loci showed high level of polymorphism with 16 alleles in total which were 5 at locus HM7, 5 at locus HM8, and 6 at locus SS1. Total allele number in population collected in Ha Giang was higher than that of Tuyen Quang, Phu Tho and Hai Duong populations. The mean of number of observed alleles (Na = 3,83 ± 0,24) was higher than the mean number of effective alleles (Ne = 2,14 ± 0,13) and low frequency alleles (< 0,1) were observed in all loci. The value of the expected heterozygosity (He = 0,38- 0,63) was lower than that of the observed heterozygosity (Ho = 0,51-0,71). FIS value was low and the genetic differences between four populations was insignificant as FST < 0,05. The results provide useful information for breeding program and conservation of the bagrid catfish in the future.